Continuous element for vibration analysis of thick shells of revolution - Cuong, Nguyen Manh; Thinh, Tran Ich (Vietnam Journal of Mechanics, 2011)
This paper presents a new numerical method: Continous Element Method (CEM) for vibration analysis of thick shells of revolution taking into account the shear deflection effects. Natural frequencies and harmonic responses of cylindrical and conical shells subjected to different boundary conditions obtained with this kind of formulation are in close agreement with finite element solutions. The main advantage is the reduction of the size of the model thus allows the high precision in the results for a large frequency range.